1991
DOI: 10.1007/bf01789047
|View full text |Cite
|
Sign up to set email alerts
|

Generation of lymphokine-activated killer cells in human ovarian carcinoma ascitic fluid: Identification of transforming growth factor-β as a suppressive factor

Abstract: The effect of cell-free ascitic fluid from patients with epithelial ovarian carcinoma on the generation of lymphokine-activated killer cells (LAK) was compared to the activity generated in control medium containing 10% fetal bovine serum, using Daudi target cells. Samples of ascitic fluid from nine different patients tested inhibited LAK generation. Suppressive activity was evident as early as 24 h of incubation in the presence of ascitic fluid and increasing suppression developed with prolonged exposure. Supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

1992
1992
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(33 citation statements)
references
References 26 publications
1
32
0
Order By: Relevance
“…Immune suppression mediated by TGF-b appears to be due to impairment of IL-2R function and suppression of high affinity IL-2R expression, 29 inhibition of natural killer cells (NK) and lymphokine-activated killer cells (LAK) induction and proliferation, 30,31 and the inhibition of maturation and antigen presentation of dendritic cells. 32,33 However, effector cells, once they become activated, are refractory to the immune inhibitory properties of TGF-b and are capable of targeting and destroying tumor cells that continue to secrete TGF-b.…”
Section: Discussionmentioning
confidence: 99%
“…Immune suppression mediated by TGF-b appears to be due to impairment of IL-2R function and suppression of high affinity IL-2R expression, 29 inhibition of natural killer cells (NK) and lymphokine-activated killer cells (LAK) induction and proliferation, 30,31 and the inhibition of maturation and antigen presentation of dendritic cells. 32,33 However, effector cells, once they become activated, are refractory to the immune inhibitory properties of TGF-b and are capable of targeting and destroying tumor cells that continue to secrete TGF-b.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, IFN-␥ secretion by CD4 ϩ T cells has been proposed to be important in vivo for the anti-tumor effects of CD4 ϩ T cells (18,19). IFN-␥ can enhance MHC class I and II expression (19,20), inhibit tumor cell proliferation (21,22), activate macrophages (23)(24)(25), inhibit the production of immunosuppressive molecules (26,27), and enhance the secretion of antiangiogenic chemokines (28 -30). However, recent studies by us (31) and others have also shown that IFN-␥ has the potential to modulate tumor cells to prevent the presentation of tumor Ags either through the down-regulation of tumor Ag protein expression or by less efficient processing of tumor Ags upon IFN-␥-dependent induction of the immunoproteasome (32).…”
Section: Ifn-␥-dependent Inhibition Of Tumor Angiogenesis Bymentioning
confidence: 99%
“…Expression of all three mammalian isotypes of TGF-β has been identified in ovarian tumors (Henriksen et al 1995) and high levels of TGF-β that are inhibitory to LAK cells have been identified in ovarian cancer ascites (Hirte & Clark 1991). TGF-β isotypes are known inhibitors of immunological processes, although precise differences between the isotypes in immunological suppression have not been characterized.…”
Section: The Role Of Immunoinhibitory Cytokines In Ovarian Cancermentioning
confidence: 99%